Albert G. Spalding and the business of baseball. Issue 9 (1st September 2020) - Swanson, Ryan
Abstract: Albert G. Spalding revolutionized the business of baseball during the late 19th and early 20th centuries. He built a retail empire based off his reputation as a player, his connections to MLB, and his ability to market directly to consumers.